Import Substitution in the Belgorod Region in the Context of Economic Security - STRYABKOVA, Elena Anatolyevna; KULIK, Anna Mikhailovna; GERASIMOVA, Natalya Anatolyevna; DRUZHNIKOVA, Elena Petrovna; KOGTEVA, Anna Nikolaevna (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017, 2018)
Today the issue regarding the need for import substitution has become particularly relevant in consequence of the application of economic sanctions against Russia in 2014, as well as the subsequent decrease in prices of primary recourses, sharp depreciation of the Russian ruble against world currencies, the blocking of access to credits on international financial markets, and termination of technology transfer. This has led the Russian economy to such a situation, where the issue arose about the need of mobilizing internal resources to support the economy and prevent its collapse. The present article uses scientific methods and general scientific principles of dialectical development and systematic approach. The major results concern the estimation of the food basket in the Belgorod region, discussions on the current status of the regional import substitution system, an evaluation of the effectiveness of state regulation measures of the import substitution policy, the formation of priority guidelines of import substitution in the context of increasing economic security of the Belgorod region.